New and little-known bryozoans from Monte León Formation (early Miocene, Argentina) and their paleobiogeographic relationships - Pérez, Leandro Martín (2015)
The bryozoan fauna from the South American Cenozoic is poorly known. The study of new material collected in the Monte León Formation (early Miocene), gave us the opportunity to describe four new species: Valdemunitella canui n. sp., Foveolaria praecursor n. sp., Neothoa reptans n. sp., and Calyptotheca santacruzana n. sp. Two of them (V. canui and C. santacruzana) were first recorded by F. Canu and interpreted as recent species from the Australian bryozoan fauna, but are herein described as new species. The stratigraphic range of Otionella parvula (Canu, 1904) is extended to the early Miocene. The present study emphasizes the close relationships between the South American Neogene bryozoan faunas and those of other Gondwanan sub-continents such as New Zealand and Australia.